Serial PID Controller for Intervehicle Distance - Indrawati, Veronica (Jurnal Otomasi Kontrol dan Instrumentasi, 2022)
This paper presents a serial PID control used to maintain the distance between vehicles running in formation in one dimension, forming a platoon-completed multi-agent system concept. Not all vehicles are equipped with inter-vehicle communication devices, so the proposed platooning control system utilizes electronic devices in the form of distance and velocity sensors existing in the vehicle to help keep the distance between vehicles constants. First discussed is the position control and velocity for a single vehicle, the model of the system is analyzed to get the PID controller parameters. Next is the problem of platooning the system on multiple vehicles using serial PID as a controller and analyzing the controller parameters for the entire system. Finally, a simulation is performed to verify the controller design that has been obtained. The simulation results show that the serial PID controller is suitable for the intervehicle distance problem.